2012
DOI: 10.1208/s12249-012-9835-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Four Types of Disintegrants and their Effect on the Spironolactone Release Properties

Abstract: Abstract. Spironolactone is a drug derived from sterols that exhibits an incomplete oral absorption due to its low water solubility and slow dissolution rate. In this study, formulations of spironolactone with four disintegrants named as croscarmellose sodium, crospovidone, sodium starch glycolate and microcrystalline cellulose II (MCCII) were conducted. The effect of those disintegrants on the tensile strength, disintegration time and dissolution rate of spironolactone-based compacts was evaluated using a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 17 publications
(14 reference statements)
2
58
0
1
Order By: Relevance
“…The fastest dissolution was observed in samples with Kollidon Õ , which showed also the best disintegration properties. The similar results were given in the study performed by Rojas et al 45 dealing with spironolactone tablets. Also Preetha et al 46 observed that tablet with crospovidone released the drug faster than tablets with sodium starch glycolate or croscarmellose sodium.…”
Section: In Vitro Dissolution Studiessupporting
confidence: 88%
“…The fastest dissolution was observed in samples with Kollidon Õ , which showed also the best disintegration properties. The similar results were given in the study performed by Rojas et al 45 dealing with spironolactone tablets. Also Preetha et al 46 observed that tablet with crospovidone released the drug faster than tablets with sodium starch glycolate or croscarmellose sodium.…”
Section: In Vitro Dissolution Studiessupporting
confidence: 88%
“…As water is absorbed into the interior of particle pores, polymer chains expand into a three-dimensional network in which water is retained. Large three-dimensional swelling of carboxymethyl starch par- ticles was reported, whereas another superdisintegrant, croscarmellose sodium, is able to swell in three dimensions only partially and its swelling ability is therefore lower (20). Slow release in the PEG sample may be attributed to the osmotic effect of polyethylene glycol, which is probably less effective in higher coating concentrations than the swelling ability of disintegrants.…”
Section: In Vitro Glucose Releasementioning
confidence: 99%
“…22 Quick water uptake and good swelling ability of CCS and SSG is ascribed to the carboxylic moieties in their structure which upon hydration results in gelation. 23 Particle size and amorphous content in the disintegrant may also affect easy water accessibility.…”
Section: Discussionmentioning
confidence: 99%